Interleukin-2 receptor activation by an anti-IL-2Rβ/γc bispecific antibody - Brauer, Peter (Nanyang Technological University, 2016)
Interleukin-2 (IL-2) is an immunostimulatory cytokine that acts as a mitogen for T cells and natural killer (NK) cells. There is an increasing interest in using IL-2 as a therapeutic agent to combat cancers and infectious pathogens. However, it has not been successfully utilized in a clinical setting to date due to a number of reasons. IL-2 signals via the IL-2 receptor complex (IL-2R), comprising three subunits - IL-2Rα (CD25), IL-2Rβ (CD122), and IL-2Rγ (CD132, common γ chain, γc). IL-2Rα binds IL-2, presenting the cytokine to IL-2Rβ and γc, which form the high-affinity IL-2R resulting in downstream signaling. IL-2R formed without IL-2Rα has a low affinity for IL-2 thereby IL-2Rα negative cells are less IL-2 stimulated. The three subunits are differentially expressed on T cell subsets, with regulatory T cells (Treg) expressing large amounts of IL-2Rα and relatively low amounts of IL-2Rβ and γc. Therefore, IL-2 therapy can stimulate Treg that interfere with effector cell immune function. In addition, IL-2 is highly toxic in effective doses and causes lung edema as a part of Vascular Leakage Syndrome (VLS). In this study, a novel approach to bypass IL2Rα-dependent Treg stimulation and toxicity by an IL-2 mimicking agonistic bispecific antibody (bAb) was investigated. This thesis shows that an anti-IL-2Rβ/γc bAb stimulates Treg and other T cells expressing IL-2Rα less preferentially, and promotes the growth of an IL-2 dependent lymphocyte cell line. Our work demonstrates a roadmap to design bAb with agonism for heterodimeric receptors such as γc containing cytokine receptors.